Multifunctionality in Mediterranean landscapes–past and future - Pinto-Correia, T.; Vos, Willem (The New Dimensions of the European Landscapes, 2004)
During past decades many of the traditional multifunctional Mediterranean landscapes with their typical complexes of agro-, silvo- and pastoral components changed thoroughly. Nowadays only few of them are still vital. Their complex farming systems secure at the same time a multitude of other functions than just agricultural production, such as support for recreation, amenity, cultural identity, preservation of natural resources and environmental quality. Some of these unique, old Mediterranean landscapes are discussed. They cover a broad range from near-tonature high mountain landscapes and terraced small-scale submediterranean polyculture landscapes to dry Mediterranean agro-silvo-pastoral landscapes. All these are changing, either spontaneously due to changing socio-economic and cultural conditions, or as a result of conscious policies, with the Common Agricultural Policy as a main driver. Even measures created to support specific traditional land uses and their landscapes are often not successful as they focus on only a part of the system. These policies and measures will not hold the valuable traditional systems from collapsing and subsequent vanishing. Some other policy instruments, such as those in forestry, are not meant to support them, but to transform them in favour of new monofunctionality. New strategies and instruments ought to deal with these multifunctional landscapes in a more integrated way, if some of them are to be maintained or transformed into others with similar qualities.
The following values have no corresponding Zotero field: periodical: The New Dimensions of the European Landscapes
Keywords: agri-environmental; agro-silvo-pastoral; CAP; landscape; Mediterranean; multifunctionality

Multifunctionality in Mediterranean landscapes–past and future - Pinto-Correia, T; Vos, Willem (The New Dimensions of the European Landscapes, 2004)
During past decades many of the traditional multifunctional Mediterranean landscapes with their typical complexes of agro-, silvo- and pastoral components changed thoroughly. Nowadays only few of them are still vital. Their complex farming systems secure at the same time a multitude of other functions than just agricultural production, such as support for recreation, amenity, cultural identity, preservation of natural resources and environmental quality. Some of these unique, old Mediterranean landscapes are discussed. They cover a broad range from near-tonature high mountain landscapes and terraced small-scale submediterranean polyculture landscapes to dry Mediterranean agro-silvo-pastoral landscapes. All these are changing, either spontaneously due to changing socio-economic and cultural conditions, or as a result of conscious policies, with the Common Agricultural Policy as a main driver. Even measures created to support specific traditional land uses and their landscapes are often not successful as they focus on only a part of the system. These policies and measures will not hold the valuable traditional systems from collapsing and subsequent vanishing. Some other policy instruments, such as those in forestry, are not meant to support them, but to transform them in favour of new monofunctionality. New strategies and instruments ought to deal with these multifunctional landscapes in a more integrated way, if some of them are to be maintained or transformed into others with similar qualities.
Keywords: agri-environmental; agro-silvo-pastoral; CAP; landscape; Mediterranean; multifunctionality

ESTUDIO EXPERIMENTAL DE LAS CARACTERISTICAS FISICO-MECANICAS DE LOS TAPONES DE CORCHO NATURAL - Hernández Fernández, Antonio (Congreso Forestal Español, Lourizán - Pontevedra. 1993, 1993)
The present experimental study tries to evaluate the best way to cuantify cap natural cork quality by standardized experiments measuring different physical and chemical parameters. Within the cork sector, the cap industry is the broadest extended and the most representative, since it represents the most significant manufacture. Its economic value is a 70-80% of the final sale price. This study is referred to the cilindric cap, made from natural cork, boiled in water at 100°C, at atmospheric pressure.
Keywords: CAP; Cork; Physical and Chemical parameters; Standardization